Green Tourism Concept on Mangrove Ecotourism in Lembung Village, Galis District, Pamekasan Regency - Nur Amalia; Darul Islam; Citra Lutfia (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
This research analyzes the implementation strategy of green tourism used to promote mangrove tourism in Lembung Village, Galis District, Pamekasan Regency. The implementation of these strategies is expected to reduce environmental damage and increase personal, organizational and regional income. The research objectives are to analyze the condition of mangrove ecotourism, analyze the application of green tourism strategies and the economic and social impacts of the application of green tourism in Lembung Village, Galis District, Pamekasan Regency. The research method uses a qualitative approach with data collection methods, namely interviews, questionnaires and observations. The results of this study will describe the research objectives and strategies for implementing green tourism on mangrove ecotourism in Lembung Village, Galis District, Pamekasan Regency. Keywords: green etourism, Mangrove, Ecotourism and strategy